Political allegiance after European integration - White, Jonathan (Houndmills, Basingstoke, Hampshire ; New York : Palgrave Macmillan, 2011)
"How should political community be seen in the context of European integration? This book combines a theoretical treatment of political allegiance with a study of ordinary citizens, examining how taxi-drivers in Britain, Germany and the Czech Republic talk politics and situate themselves relative to political institutions and other citizens"--
Political ommunity and the bonds of collectivity -- Studying the allegiances of Europeans -- Articulations of the political common -- On subjects, opponents and counterparts -- The credibility of political projects -- The place of Europe and the EU -- European integration off the meter -- Methodological appendix.
Keywords: Allegiance; European federation